2016
DOI: 10.1007/s00246-016-1379-6
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Timing of ECMO Initiation on Outcomes After Pediatric Heart Surgery: A Multi-Institutional Analysis

Abstract: Little is known about the relationship of timing of extracorporeal membrane oxygenation (ECMO) initiation on patient outcomes after pediatric heart surgery. We hypothesized that increasing timing of ECMO initiation after heart surgery will be associated with worsening study outcomes. Patients aged ≤18 years receiving ECMO after pediatric cardiac surgery at a Pediatric Health Information System-participating hospital (2004-2013) were included. Outcomes evaluated included in-hospital mortality, composite poor ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
46
1
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(62 citation statements)
references
References 10 publications
7
46
1
5
Order By: Relevance
“…We anticipated that survival would steadily decrease with treatment duration as progression of disease and treatment complications added to cumulative mortality, as suggested previously [8]. However, we found that survival in fact increases in the first few days, peaking mid-week in the first week of treatment.…”
Section: Discussionsupporting
confidence: 66%
“…We anticipated that survival would steadily decrease with treatment duration as progression of disease and treatment complications added to cumulative mortality, as suggested previously [8]. However, we found that survival in fact increases in the first few days, peaking mid-week in the first week of treatment.…”
Section: Discussionsupporting
confidence: 66%
“…Longer duration of ECMO support is associated with increased mortality in children after cardiac surgery 18. In our series, median ECMO duration was 12 (3.5–24) days and we observed an increased incidence of thrombotic complications.…”
Section: Discussionsupporting
confidence: 46%
“…Initially starting from 1970s, the usage of ECMO in pediatric cardiac surgery has gradually increased over the last 40 years (1,2). The most common indications for ECMO usage in postoperative pediatric cardiac cases are low cardiac output syndrome, pulmonary hypertension, inotropic refractory cardiogenic shock, inability to weaning from cardiopulmonary bypass, bridging to cardiac transplantation and extracorporeal cardiopulmonary resuscitation.…”
Section: Introductionmentioning
confidence: 99%